Some aspects of laser and other alternative technologies use for metal cutting - Milikić, Dragoje; Kovač, Pavel; Krajny, Zdenko (Journal of Production Engineering, 1991)
In the paper short review of world’s industrial laser system production and the future trend in their development is presented. Aspiration of the paper I to make comparative analyses of material cutting with CO2-laser and with other alternative technologies. From that we can conclude which are the good and the bad points of cutting with CO2-laser. The biggest concurrent to this cutting process, in the future, will be cutting with abrasive-water jet, is emphasized.